2021
DOI: 10.3389/fpsyt.2021.804967
|View full text |Cite
|
Sign up to set email alerts
|

Medical Students Show Lower Physical Activity Levels and Higher Anxiety Than Physical Education Students: A Cross-Sectional Study During the COVID-19 Pandemic

Abstract: Objective: This study aimed to compare the time in physical activity (PA) [light (LPA), moderate and vigorous (MVPA)] and sedentary behavior (SB) (weekdays, weekends, or both) between Medical (MED) and Physical Education (PE) students who underwent remote classes imposed by the COVID-19. In addition, we compared symptoms of depression and anxiety and sleep quality.Methods: A cross-sectional study (272 MED and 95 PE students). The International Physical Activity Questionnaire (IPAQ), Beck Inventory (Anxiety, De… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 48 publications
3
10
0
Order By: Relevance
“…Third, more engagement in physical activity might be another reason for the better mental well-being of medical students; this was supported by some previous studies, which demonstrated that physical activity was negatively associated with mental distress [ 86 ] and that medical students reported a higher level of physical activity during the lockdown [ 87 ]. This finding was also supported by another cross-sectional study, in which medical students engaged in less physical activity and showed a higher level of anxiety compared to students engaging in high levels of physical activity [ 63 ]. Based on our findings, timely psychological counseling and intervention, especially for non-medical students, are required.…”
Section: Discussionsupporting
confidence: 60%
See 1 more Smart Citation
“…Third, more engagement in physical activity might be another reason for the better mental well-being of medical students; this was supported by some previous studies, which demonstrated that physical activity was negatively associated with mental distress [ 86 ] and that medical students reported a higher level of physical activity during the lockdown [ 87 ]. This finding was also supported by another cross-sectional study, in which medical students engaged in less physical activity and showed a higher level of anxiety compared to students engaging in high levels of physical activity [ 63 ]. Based on our findings, timely psychological counseling and intervention, especially for non-medical students, are required.…”
Section: Discussionsupporting
confidence: 60%
“…Moreover, after the outbreak of COVID-19, 11 out of 14 studies reported that medical students had better or similar mental health status in China, Poland, France, Saudi Arabia, and Turkey, when compared with non-medical students [ 49 , 66–75 ], which was in line with our study. Only three studies showed a significantly higher level of depression symptoms, anxiety symptoms, and stress among medical students [ 63 , 76 , 77 ]. Taken together, the above findings might suggest that medical students were not at a higher risk of mental distress compared with their peers in non-medical majors.…”
Section: Discussionmentioning
confidence: 99%
“… Muñoz-Bullón et al (2017) compared the academic performance of sports participants with that of non-participants and found that participation in formal sports had a positive impact on students’ higher grades. In terms of the psychological impact of sports encounters on students, de Souza et al (2021) compared sports students with medical students and pointed out that medical students had higher anxiety values than sports students during the COVID-19 epidemic. This may be because physical activity reduces trait anxiety ( Felez-Nobrega et al, 2020 ).…”
Section: Related Research and Theoretical Frameworkmentioning
confidence: 99%
“…A meta-analysis of college Students' sleep and physical activity found that most studies did not find a link between sleep and physical activity in college students (Memon et al, 2021), which is in accordance with the results of this study. Similarly, a study comparing the sleep quality of medical students and sports students also showed that there was no significant difference in the two (de Souza et al, 2021).…”
Section: Discussionmentioning
confidence: 97%